2021
DOI: 10.1186/s12906-021-03452-6
|View full text |Cite
|
Sign up to set email alerts
|

Ficus deltoidea ameliorates biochemical, hormonal, and histomorphometric changes in letrozole-induced polycystic ovarian syndrome rats

Abstract: Background Insulin resistance and hormonal imbalances are key features in the pathophysiology of polycystic ovarian syndrome (PCOS). We have previously shown that Ficus deltoidea var. deltoidea Jack (Moraceae) can improve insulin sensitivity and hormonal profile in PCOS female rats. However, biological characteristics underpinning the therapeutic effects of F. deltoidea for treating PCOS remain to be clarified. This study aims to investigate the biochemical, hormonal, and histomorphometric chan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 59 publications
(42 reference statements)
2
10
1
Order By: Relevance
“…Therefore, a new treatment strategy with less side effects, more affordable, and with more pleiotropic activity is required. Previous studies have documented the efficacy of several herbal medications such as resveratrol, 15 quercetin, 16 thymoquinone 17 and Ficus deltoidea 18 in restoring function of the ovaries, insulin sensitivity and hormonal profile in experimentally induced PCOS. These studies suggested that the herbal medicines with ovulatory and hypoglycemic effects might be considered as an alternative therapy for PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a new treatment strategy with less side effects, more affordable, and with more pleiotropic activity is required. Previous studies have documented the efficacy of several herbal medications such as resveratrol, 15 quercetin, 16 thymoquinone 17 and Ficus deltoidea 18 in restoring function of the ovaries, insulin sensitivity and hormonal profile in experimentally induced PCOS. These studies suggested that the herbal medicines with ovulatory and hypoglycemic effects might be considered as an alternative therapy for PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…Histomorphometric measurements confirmed that F. deltoidea increased the corpus luteum number and the endometrial thickness. These findings suggest the potential use of F. deltoidea as an adjuvant agent in the treatment program of PCOS [17].…”
Section: Resultsmentioning
confidence: 71%
“…Haslan M.A. and co-workers [17] investigated the biochemical, hormonal, and histomorphometric changes in letrozole (LTZ)-induced PCOS female rats following treatment with F. deltoidea. The results showed that treatment with F. deltoidea at the dose of 500 and 1000 mg/kg/day reduced insulin resistance, obesity indices, total cholesterol, triglycerides, low-density lipoprotein cholesterol (LDL), malonic dialdehyde (MDA), testosterone, luteinizing hormone (LH), and follicle-stimulating hormone (FSH) to nearnormal levels in PCOS rats.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 30 female mice (Mus musculus) at 3 months age, and weighing 30-40 grams (Lee's Index Value > 0.3) were divided randomly into three groups of 10, namely CTRL (n = 10, control without intervention), MISEM (n = 10, moderateintensity swimming exercise in the morning), and MISEN (n = 10, moderate-intensity swimming exercise in the night). Mice (Mus musculus) were placed in temperature-controlled steel cages (20-22 °C, 55-65% humidity) with a 12-h light/dark cycle (Haslan et al, 2021). This research has followed animal welfare principles published by the European Convention for the Protection of Vertebrate Animals.…”
Section: Experimental Designmentioning
confidence: 99%